Genetic divergence in the Indian Mackerel Ra, trelliger kanagurta (Cuv) from the coastal waters of Peninsular India and the Andaman Sea - Menezes, Maria R; Naik, Sandeep; Martins, Maria (Indian Journal of Fisheries, 2011)
One important consideration in the commercial exploitation of a fishery resource is the identificat;on of any discrete population or stock units. These stock units are usually selfmaintaining groups offish that are temporally or spatially isolated from one another. Because of their isolation it is assumed that they are genetically distinct (Booke 1981).